Critical Juridical Analysis of Criminal and Medical Boundaries in the Handling of Narcotics Addicts in Indonesia - I Kadek Bagus Pradana Putra (Indonesian Journal of Law and Justice, 2026)
The drug problem in Indonesia constitutes a complex and multidimensional phenomenon, intersecting issues of criminal justice and public health. The handling of drug addicts remains characterized by a persistent dichotomy between punitive legal approaches and therapeutic interventions, which often results in legal uncertainty, inconsistent law enforcement practices, and enduring social stigmatization. This study aims to analyze the regulatory framework governing the treatment of drug addicts in Indonesia and to formulate an integrated model that reconciles legal accountability with health-oriented recovery. This research employs a normative juridical (doctrinal) method, relying on a comprehensive literature review and qualitative analysis of primary and secondary legal materials. These include statutory regulations, Supreme Court Circular Letters (SEMA), prosecutorial guidelines, as well as institutional policies issued by the National Narcotics Agency (BNN) and the Indonesian National Police (Polri). The analytical approach focuses on identifying normative inconsistencies and evaluating the extent to which existing regulations support a rehabilitative paradigm. The findings indicate that the current legal framework formally adopts a dual-track system, recognizing both criminal sanctions and medical-social rehabilitation as legitimate responses to drug abuse. However, its implementation remains fragmented and lacks effective inter-institutional coordination. In response, this study proposes an integrated treatment model that incorporates diversified sentencing mechanisms, restorative justice principles, and synergistic coordination across legal, medical, and social sectors. In conclusion, the proposed model offers a more balanced and holistic approach to drug policy by reducing over-criminalization, enhancing rehabilitation outcomes, and strengthening legal certainty. This integrative framework is expected to contribute to a more humane and effective system for addressing drug addiction in Indonesia.